2020
DOI: 10.1002/adsu.201900112
|View full text |Cite
|
Sign up to set email alerts
|

Alginate‐Derived Active Blend Enhances Adsorption and Photocatalytic Removal of Organic Pollutants in Water

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Further promising fields of applications of PCMs encompass smart catalysts for environmental remediation [ 130 , 131 , 132 , 133 ] and system chemistry applied to solid-state devices [ 134 ]. Broadening the horizons of research could stimulate the discovery and development of new materials and architectures, with major, yet unpredictable benefits for different areas of application.…”
Section: Discussionmentioning
confidence: 99%
“…Further promising fields of applications of PCMs encompass smart catalysts for environmental remediation [ 130 , 131 , 132 , 133 ] and system chemistry applied to solid-state devices [ 134 ]. Broadening the horizons of research could stimulate the discovery and development of new materials and architectures, with major, yet unpredictable benefits for different areas of application.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable materials can offer several opportunities to depollute water, as the synthesis of safe adsorbent materials derived from waste [ 45 , 46 ]. New strategies for pollutants removal allowed also the synthesis of alginate-derived blend [ 47 ], obtained without any commercial additives. These new materials show a high performance in the sequestration of pollutants in water matrices (SDG 6).…”
Section: Sustainable Materials Developed By the Instm Consortiummentioning
confidence: 99%
“…Recent works of INSTM research groups demonstrated that a rational design of remediation systems inspired by criteria of sustainability and green chemistry can help to advance detection and removal of a variety of persistent organic pollutants from water. In this context, alginate-based smart sponges play a key role and open exciting opportunities for future applications [ 47 ]. Additionally, porous materials were synthesized to obtain membranes and foams [ 48 ], with good results as an adsorbent to remove heavy metals.…”
Section: Sustainable Materials Developed By the Instm Consortiummentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer supports have proved to be among the best candidates for immobilising photocatalyst nanoparticles due to their numerous advantages: low cost, ready accessibility, chemical inertness, and mechanical stability with high durability. In addition, polymer supports have relatively low density, allowing for the design of floating photocatalysts, especially in aqueous media [ 11 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%